OUTCOMES OF LAPAROSCOPIC SURGERY FOR COLORECTAL CANCER WITH TOTALLY INTRACORPOREAL ANASTOMOSIS TECHNIQUE IN ELDERLY PATIENTS - Anh Bắc, Hoàng; Tiến Dũng, Lê; Duy Đạt, Đỗ; Phan Thanh Tiến, Nguyễn (Journal of Health and Aging, 2025)
Laparoscopic surgery with totally intracorporeal anastomosis has become an advanced technique for treating colon cancer, especially in elderly patients. However, studies on its feasibility and safety in Vietnam remain limited. To evaluate the outcomes of laparoscopic colectomy with intracorporeal anastomosis in elderly patients, focusing on safety, complications, and recovery time. A cross-sectional descriptive study was conducted on 49 patients aged ≥62 who underwent laparoscopic colectomy with intracorporeal anastomosis at Thong Nhat Hospital from January 2021 to February 2025. Data included demographic characteristics, operative time, postoperative complications, and oncological results. The mean age of patients was 73.15 ± 5.26, with 63.26% male. The average operative time was 231.52 ± 49.67 minutes, and the mean blood loss was 73.59 ± 14.67 ml. The postoperative complication rate was 12.24%, including pneumonia/wound infection (6.12%), anastomotic leakage (4.08%), early obstruction (2.04%), and ileus (4.08%). The mean number of harvested lymph nodes was 9.37 ± 2.25, with 69.52% showing nodal metastasis. The average hospital stay was 11.62 ± 7.2 days. Laparoscopic surgery with totally intracorporeal anastomosis is safe and feasible for elderly patients, offering quick recovery and low complication rates.